Kaedah pengajaran pengetahuan agama islam di Brunei Darussalam - Haji Maimun Aqsha Lubis,; Roslan Hj Aspar, (penerbit ukm, 2005)
This research was conducted in secondary schools at Brunei-Muara district. Among the main purposes of the research were to find out the most popular methods and mostly used by the respective religious teachers and to identify the most effective teaching methodologies in teaching Islamic religious study. A group of 26 religious teachers and another group of 148 students were involved in this research. The research instruments, included: questionnaire for teachers and students, interview for teachers only and observation in the classroom. This study found out some of the most popular methods in the teaching of religious study, are explanation method, question and answer method, advise method and drill method. The most effective methods in teaching Islamic religious study found are advise method, memorize method, story telling method and role play method. Meanwhile, the application of these methods effected some of students’ behaviour and personality such as Islamic thought, to encourage students’ interest in learning, helping them to practice Islamic teachings, to refine their attitudes and moral values, helping them to evaluate and inculcate the Islamic values and to develop their own responsibilities for their families and society. A part from that, this research also identified that female teachers educate more effectively than male teachers.